2008
DOI: 10.1016/j.ijporl.2008.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Auditory steady-state responses to bone conduction stimuli in children with hearing loss

Abstract: SummaryObjective: The auditory steady-state response (ASSR) to air-conduction (AC) stimuli has been widely incorporated into audiological test-batteries for the pediatric population. The current understanding of ASSR to bone conduction (BC) stimuli, however, is more limited, especially in the case of infants and children. There are few reports on ASSR thresholds to BC stimuli in infants and young children, and none for infants or children with hearing loss. The objective of this study was to investigate BC ASS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 24 publications
1
11
0
1
Order By: Relevance
“…The present study has provided some insight into the mechanical properties of the skin-covered skull of infants and young children and has suggested possible links between these properties and the maturational trends we observe for bone conduction hearing sensitivity (Stapells & Ruben 1989;Nousak & Stapells 1992;Foxe & Stapells 1993;Small & Stapells 2006;Small & Stapells 2008;Swanepoel et al 2008;Hulecki & Small 2011;Casey & Small 2014). Although we have not confirmed the link between mechanical impedance differences with maturation and output to the cochlea, some of the findings from this study may have practical clinical applications.…”
Section: Discussionsupporting
confidence: 52%
“…The present study has provided some insight into the mechanical properties of the skin-covered skull of infants and young children and has suggested possible links between these properties and the maturational trends we observe for bone conduction hearing sensitivity (Stapells & Ruben 1989;Nousak & Stapells 1992;Foxe & Stapells 1993;Small & Stapells 2006;Small & Stapells 2008;Swanepoel et al 2008;Hulecki & Small 2011;Casey & Small 2014). Although we have not confirmed the link between mechanical impedance differences with maturation and output to the cochlea, some of the findings from this study may have practical clinical applications.…”
Section: Discussionsupporting
confidence: 52%
“…There are several studies that have reported BC ASSR thresholds in individuals with normal hearing which consistently show that thresholds are better in the low frequencies compared with the high frequencies in young and older infants compared with the frequencies in adults (e.g., Small & Stapells 2006. However, there is currently only one published study that estimated BC ASSRs in children with hearing loss (Swanepoel et al 2008). This study provides relatively limited information as it estimated thresholds for a wide age range (3 months to 11.5 years) and did not confirm the accuracy of the ASSR results by comparing thresholds with a gold standard tool.…”
Section: Introductionmentioning
confidence: 99%
“…2 Current research indicates that reliable bone conduction thresholds can be obtained in preterm, term, and older infants with normal hearing. [23][24][25][26] A maturational effect suggests that bone conduction ASSR thresholds improve in the high frequencies and deteriorate in the low frequencies as illustrated in Fig. 2.…”
Section: Air Conduction Thresholdsmentioning
confidence: 99%
“…2. A series of studies investigating the procedural factors that may influence the measurement of bone conduction ASSR thresholds in infants [23][24][25][26] recommend the following: (1) coupling the bone oscillator can be done with an elastic band or be handheld with training; (2) forehead placement should be avoided but temporal and mastoid placement is appropriate; (3) occlusion does not have a significant effect on threshold estimation; (4) interaural attenuation for infants with bone conduction is greater than for adults (at least 10 to 30 dB), making isolation of the test cochlea easier.…”
Section: Air Conduction Thresholdsmentioning
confidence: 99%